Identification of the presence of the mutation of the gene of PKD not associated of HCM in Persian cats - case report - Arruda, Vanesa Kutz de [UNESP] (2015)
Polycystic kidney disease (PKD) is a hereditary autosomal dominant disorder that mainly affects Persian cats; it is an important cause of chronic kidney disease in this species. Hypertrophic cardiomyopathy (HCM) is the most common heart disease in cats, and there is evidence of a genetic origin in some breeds. Although neither of these disorders is rare in cats, according to our literature review, this is the first report of the concomitant occurrence of PKD and HCM in Persian cats in Brazil.